2020
DOI: 10.1111/hsc.13098
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and managing care for children with autism spectrum disorders in general practice: A systematic review and narrative synthesis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…This allows for ideas from the existing literature to be brought together with data derived from the interviews to develop an analytical framework. This included a recent systematic review on autism in general practice 10 and a review by Tatlow-Golden et al 6 on GPs and ADHD. All interviews were transcribed by BC or a professional transcription service.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows for ideas from the existing literature to be brought together with data derived from the interviews to develop an analytical framework. This included a recent systematic review on autism in general practice 10 and a review by Tatlow-Golden et al 6 on GPs and ADHD. All interviews were transcribed by BC or a professional transcription service.…”
Section: Methodsmentioning
confidence: 99%
“…Survey work indicates that in general GPs have a sound understanding of autism but little confidence responding to the condition 7. Still, review work on GPs’ knowledge of autism and ADHD has identified some outmoded aetiological theories still receiving endorsement 6 10. Consequently, calls for training from GPs and researchers alike are recurrent in much of this work.…”
Section: Introductionmentioning
confidence: 99%
“…They do not know of any tools to improve communication with the ASD’s people. Finally, they did not know of a clearly defined care pathway for the follow-up of the autistic person [ 14 ]. If we put our results into the perspective of French guidelines, we can see that the GPs refer their patients easily when there is a behavioural disorder.…”
Section: Discussionmentioning
confidence: 99%
“…At one end of the continuum were GPs who had not heard of autism or who endorsed outdated etiological theories. On the other hand, GPs had a good knowledge of the disorder but limited confidence in their ability to identify it [ 14 ]. Thus, the GMs are concerned.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals who assess child development should have a sound understanding of autism. 22 It is also important for all clinicians involved in patient care to recognise red flags of ASD so that early referral and intervention can be made. 23 To date, few studies have been carried out to assess knowledge and beliefs about ASD among physicians in China.…”
Section: What This Study Addsmentioning
confidence: 99%